Catalogue of the timber forest species of the Amazon and the Peruvian Yunga - Vásquez Martínez, Rodolfo (2022)
Due to its privileged location, in the centre of the Andes Mountains, Peru has a vast strip of the Yunga and to the east an immense Amazonian plain, where a high diversity of timber species grows, of which knowledge of their taxonomy is still incipient. For this reason, the main objective of this study was to compile scattered information on the taxonomy of timber species and compare it with our field observations, at the same time proposing a group of species that could be timber in the soon future. A final list of 1 311 species was obtained, based on the catalogue of trees in Peru, the specialized literature that documents the use of timber species, the official list of forest species, and our field observations made over the last 15 years. The family with the largest number of species is Fabaceae, with 156 species, and the region with the largest number of species is Loreto, with 927 species, considered the region with the largest territorial extension.